AI-Based Learning Media “Toori” (Dance Cartoon) to Increase Elementary School Students’ Interest in Learning Dance Arts - Prayoga, Viona Regina; Nurharini, Atip (Jurnal Ilmiah Pendidikan Profesi Guru, 2024)
Art education in the digital era faces many issues that need to be addressed to ensure that students continue to benefit from quality and contextually relevant art learning experiences. This study aims to develop AI-based “Toori” (Kartoon Dance) learning media to increase elementary school students' interest in learning dance. The type of research used is Research and Development (R&D). This study uses a model according to Borg and Gall. The subjects of the study were media experts and material experts. The trial subjects in this study were 38 students of grade IV of IMAMA Elementary School. The methods used in collecting data were observation, interviews, questionnaires, documentation, and tests. The data collection instruments used questionnaire sheets and test questions. The techniques used to analyze the data were qualitative, quantitative, descriptive analysis, and inferential statistics. The study's results were the assessment results of learning media experts, namely 91.17% (very good) and learning material experts, namely 95% (very good). The t-test results showed a significant difference between the average pretest score and the average posttest score. The results of the N-gain test showed that the effectiveness was included in the reasonably effective category. It is concluded that the AI-based learning media “Toori” (Dance Cartoon) can increase students' interest in learning art.